Pengaruh Citra Merek, Kualitas Produk dan Lokasi terhadap Keputusan Pembelian di Drumstairs : - - Mochammad Khadafi; Darwin Raja Unggul Saragih (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Abstract: This study aims to determine the effect of brand image, product quality, and location on purchasing decisions at the Drumstairs Restaurant. This study uses a quantitative approach with a survey method. The population in this study were all customers who came to the Drumstairs Restaurant, with a total of 104 respondents. The sampling technique used was purposive sampling, which is determining the sample based on certain criteria that are relevant to the research objectives. Data analysis was carried out using multiple linear regression through the assistance of SPSS software version 26. The results of the study showed that brand image had a positive and significant effect on purchasing decisions. However, product quality did not show a significant effect on purchasing decisions. Meanwhile, location was also found to have a positive and significant effect on purchasing decisions. Simultaneously, the brand image and location variables together had a positive and significant effect on purchasing decisions, while the product quality variable did not have a significant effect. These findings indicate that in the context of the Drumstairs Restaurant, aspects of brand image and ease of location access are more decisive in influencing consumer purchasing behavior than product quality. Therefore, restaurant management is advised to continue to strengthen brand image and choose strategic locations in order to improve customer purchasing decisions.